Atomistic investigation of effect of alloying on mechanical properties and microstructural evolution of ternary FeCo-X (X = V, Nb, Mo, W) - Muralles, Mario (2024)
This atomistic simulation study delves into the impact of V, Nb, Mo, and W on the mechanical properties of equiatomic FeCo, employing the modified embedded atom method (MEAM). An analysis of individual effects on antiphase boundary (APB) energies reveals a consistent reduction along preferred slip planes, except for Nb. Monte Carlo-molecular dynamics (MC-MD) simulations were used to explore the diffusion behavior of these solutes, highlighting their dynamic interactions and preference to migrate into the grain boundaries (GB). Tensile simulations conducted on nanocrystalline (NC) models oriented in different directions unveil comparable stress–strain curves, displaying continuous yielding with a humpy yield curve that varies with the straining orientation. Notably, W emerged as the most effective addition enhancing the ultimate tensile strength (UTS). Microcrack nucleation development differ depending on the straining direction. In binary FeCo and in the alloy with Mo additions, void development was observed at grain boundary (GB) triple junctions, while with V and W additions, it occurred at the intersection of a slip band and a GB, with limited propagation in both scenarios. In contrast, Nb additions show enhanced stress accommodation through slip band formation within grains, preventing microcrack development. These discoveries offer valuable insights on the impact of alloying elements on the mechanical behavior of ternary FeCo-X (X = V, Nb, Mo, W) alloys.